2012
DOI: 10.5433/1679-0359.2012v33supl1p2775
|View full text |Cite
|
Sign up to set email alerts
|

Estoque de carbono orgânico no solo afetado por adubação orgânica e sistemas de culturas no Sul do Brasil

Abstract: Organic carbon is a major component of soil organic matter and its stock is influenced by the management system adopted. This study aimed to examine the effects of cropping systems and nutrient sources (mineral and organic) on the concentrations and storage of soil organic carbon in no-tillage system. The experiment was carried out in Mercedes, Parana, Brazil, in an Nitossolo Vermelho (Alfisol) from October 2007 to September 2009. The treatments consisted of four crop succession systems: (1) soybean/wheat/corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Moreover, other studies agree that the resulting charcoal in the soil due to the use of fire would contribute to increases in contents of more recalcitrant soil compartments (STEINER et al, 2012) and decreases in more labile ones, such as POC. This effect was found in the present study, since the treatments showed higher MAOC than POC contents (Table 2), mainly in the surface layers with the use of fire.…”
Section: Resultsmentioning
confidence: 86%
“…Moreover, other studies agree that the resulting charcoal in the soil due to the use of fire would contribute to increases in contents of more recalcitrant soil compartments (STEINER et al, 2012) and decreases in more labile ones, such as POC. This effect was found in the present study, since the treatments showed higher MAOC than POC contents (Table 2), mainly in the surface layers with the use of fire.…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, the addition of organic sources has a high capacity to increase the soil's organic carbon stock, due to the entry of organic matter, in addition to increasing the availability of nutrients. Steiner et al (2012), states that the soil organic carbon stock can be altered with greater or lesser intensity, as it is one of the most sensitive properties affected by management descisions. A reduction in the initial content for this element was observed from the planting of cassava, according to Yada et al (2015), the low levels for this element are related to the removal of the natural cover from the soil for the farm, reducing the capacity of recovery of soil chemical characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The results of TOC and N indicate that the input of organic fertilization may have contributed to a smaller reduction, because similar results of TOC between E35 and NF were verified in the surface layers. Analyzing the effects of swine waste application under different cropping systems, Steiner et al (2012) andCastro Filho et al (2003) found an increase in soil organic carbon content.…”
Section: Discussionmentioning
confidence: 99%